Single stage stirred tank bioreactor production of star fruit (Averrhoa carambola) vinegar - Abdul Karim, Mohamed Ismail; Jamal, Parveen; Abd Rahman, Mohd Nasir Jamaluddin (IIUM Press, 2011)
Vinegar was produced in the lab from fermentation of local star fruit (Averrhoa carambola) juice in stirred tank bioreactor. The fermentation of star fruit juice into vinegar was produced by decomposing sugar contained in the fruit substrate through alcohol and acetic acid fermentation over a period of three days with the aid of two microorganisms, Saccharomyces cerevisiae and Acetobactor aceti. To Study the optimization of the fermentation process, the parameter conditions used in the tank bioreactor are agitation speed, aeration and the concentration of glucose used. The design of the experiment was conducted using Design Expert software. Analysis at every 12 hours interval was carried for ethanol concentration, reducing sugar level and acetic acid. The findings in this project can be applied to produce vinegar in large amount from our local tropical star fruit juice. The experiment showed that the optimum conditions for agitation was 300 rpm, aeration at 0.5 Lpm and glucose concentration (20%) consequently produced 1.63% vinegar.